Investigating Pregnancy and Its Complications Using Circulating Cell-Free RNA in Women's Blood During Gestation - Mira N. Moufarrej; Ronald J. Wong; Gary M. Shaw; David K. Stevenson; Stephen R. Quake (Frontiers Media S.A., 2020)
In recent years, there have been major advances in the application of non-invasive techniques to predict pregnancy-related complications, for example by measuring cell-free RNA (cfRNA) in maternal blood. In contrast to cell-free DNA (cfDNA), which is already in clinical use to diagnose fetal aneuploidy, circulating RNA levels can correspond with tissue-specific gene expression and provide a snapshot of prenatal health across gestation. Here, we review the physiologic origins of cfRNA and its novel applications and corresponding challenges to monitor fetal and maternal health and predict pregnancy-related complications.